2001
DOI: 10.1165/ajrcmb.25.6.4628
|View full text |Cite
|
Sign up to set email alerts
|

Association Between IL-1 β /TNF- α –Induced Glucocorticoid-Sensitive Changes in Multiple Gene Expression and Altered Responsiveness in Airway Smooth Muscle

Abstract: The pleiotropic cytokines interleukin (IL)-1beta and tumor necrosis factor (TNF)-alpha have been implicated in the pathophysiology of asthma. To elucidate the role of these cytokines in the pro-asthmatic state, the effects of IL-1beta and TNF-alpha on airway smooth muscle (ASM) responsiveness and ASM expression of multiple genes, assessed by high-density oligonucleotide array analysis, were examined in the absence and presence of the glucocorticoid dexamethasone (DEX). Administration of IL-1beta/TNF-alpha incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
53
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 53 publications
8
53
0
Order By: Relevance
“…Ours is the first report to show that ET-1 induces CCN2 and, thus, that CCN2 could also be a downstream mediator of ET-1 activity. The ET-1 response element of the CCN2 promoter is independent of its Smad element, which is required for the TGF␤-induction of CCN2 (22,47). Instead, the ET-1 induction of CCN2 occurs through the BCE-1 element of the CCN2 promoter, which is not required for the TGF␤-induction of CCN2 (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ours is the first report to show that ET-1 induces CCN2 and, thus, that CCN2 could also be a downstream mediator of ET-1 activity. The ET-1 response element of the CCN2 promoter is independent of its Smad element, which is required for the TGF␤-induction of CCN2 (22,47). Instead, the ET-1 induction of CCN2 occurs through the BCE-1 element of the CCN2 promoter, which is not required for the TGF␤-induction of CCN2 (22).…”
Section: Discussionmentioning
confidence: 99%
“…CCN2 is a cysteine-rich, pro-adhesive, matricellular protein that plays an essential role in the formation of blood vessels, bone, and connective tissue (46). Because the expression of this protein is potently induced by TGF␤ in a Smad-dependent fashion (22), it has been hypothesized that CCN2 mediates several of the downstream actions of TGF␤ (26). Ours is the first report to show that ET-1 induces CCN2 and, thus, that CCN2 could also be a downstream mediator of ET-1 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for using this strategy is based on two well established concepts. First, the manifestations of asthma are, at least in part, channeled through the actions of IL-1␤ and TNF-␣ (11,12). Second, the efficacy of GCs in asthma is, at least in part, through its effect on the expression of genes that are modulated by proinflammatory cytokines (12,13).…”
mentioning
confidence: 99%
“…Glucocorticoids have bronchoprotective action to directly alter bronchial smooth muscle function by the following effects; 1) inhibition of bronchial smooth muscle contractility, 2) augmentation of bronchial smooth muscle relaxation, 3) suppression of bronchial smooth muscle proliferation, 4) prevention of the release of various cytokines and chemokines from stimulated bronchial smooth muscle, and other actions. 13,14,25) We previously reported that glucocorticoids might inhibit the AHR by reducing the protein expression and activation of a monometric GTP-binding protein, RhoA, which is involved in the agonist-induced Ca 2ϩ sensitization of bronchial smooth muscle contraction. 22 of inhibitory effect of glucocorticoid on the upregulation of RhoA induced by antigen-challenge.…”
Section: Discussionmentioning
confidence: 99%